Does labor force participation rates of youth vary within the business cycle? Evidence from Germany and Poland - Sophie Dunsch (European University Viadrina, Department of Business Administration and Economics, 2016)
Unemployment rates, especially among youth, have increased in various countries of Europe over the last years. As labor force participation rate is one key influence on unemployment, I estimate country specific coefficients for the responsiveness of the labor force participation rates to the business cycle for different age cohorts. The results show that an influence of the business cycle on movements of the participation rates are only statistically significant for the youngest age cohort of the 15-to-24-years old in Germany, suggesting a discouraged worker effect.
Keywords: J13; J21; C23; E32; 330; Youth Unemployment; Youth Labor Force Participation; Poland; Germany; Business Fluctuations